Symptom Burden Clustering in Chronic Kidney Disease Stage 5. - Gutiérrez-Sánchez, Daniel; Leiva Santos, Juan Pablo; Cuesta-Vargas, Antonio (SAGE, 2019)
Patients with chronic kidney disease (CKD) Stage 5, experience multiple symptoms that negatively affect the health-related quality of life (HRQoL). This study examined the cluster of symptoms and their association with disease severity and comorbidities. The study sample included 123 patients with CKD Stage 5; 60 patients were in the dialysis group and 63 patients in the Conservative Kidney Management group. Symptom data were collected using the Spanish modified version of Palliative Care Outcome Scale–Symptoms (POS-S) Renal, a validated questionnaire to assess symptoms in this population. More than half of the patients described weakness, difficulty sleeping, and feeling depressed. Two symptom clusters were identified. There was no significant statistical correlation between disease severity and symptoms and between comorbidities and symptoms. The tendency of these symptoms to occur together has implications for improving symptom management in this population. Routine symptom assessment can be useful in clinical and research settings.
Política de acceso abierto tomada de:https://v2.sherpa.ac.uk/id/publication/9066
Keywords: Insuficiencia renal crónica; Nursing; Symptoms; Evaluation; Symptom Cluster; Advanced chronic kidney disease